Beyond knowledge transfer: The role of coach developers as motivators for lifelong learning - Dohme, L.-C.; Rankin-Wright, A. J.; Lara-Bercial, S. (International Sport Coaching Journal, 2019)
Research investigating coach education and development has grown significantly over the past three decades. Most of these efforts have focused on establishing how coaches learn; yet the actual impact of specific coach education and development interventions has received considerably less attention. Moreover, the role of coach developers in facilitating this impact remains largely unknown. To address this knowledge gap, this study used a realist evaluation approach to engage in a detailed exploration of a large-scale, multi-annual coach education and development intervention with high school coaches in the Philippines. Using interviews and focus groups at two different time points with multiple stakeholders, this study established a series of context, mechanism and outcome configurations that provide a nuanced perspective on how coach education and development works. More specifically, this paper offers a novel interpretation of the role of coach developers as `motivators for lifelong learning` established through three key mechanisms: 1) being available, approachable, and supportive; 2) creating a sense of belonging; and 3) raising coaches` aspirations by increasing their sense of purpose and duty. Practical guidelines for the education of coach developers, as well as future coach education and development programmes are provided.